Sarah M. Pourciau. The Writing of Spirit: Soul, System, and the Roots of Language Science.: New York: Fordham University Press, 2017, 384pp. ISBN 978-0-823-27563-2. - Adler, Anthony Curtis (Germanic Review)
For Pourciau, it is first with structuralism so understood that the relation of "finished forms to formal principle", indeed of "structure to soul", achieves "a rigorously nonparadoxical, system-internal account" (5). And hence it is by transmogrifying the generic metaphysical spirit into the spirit I of i this or that proper name, but ultimately into the I ghost i of Wagner - which, in turn, will be exorcized by Saussure and Jakobson - that the logical coherence of structuralism will be maintained. Ultimately, moreover, the continuity and coherence of Pourciau's narrative depends on the concept of I telos i and teleology, which serves as a kind of guiding thread.